EFEKTIVITAS SEDIAAN GEL ANTISEPTIK TANGAN EKSTRAK DAUN SIRSAK Annona muricata Linn SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus epidermidis - VINCENTIA ADE RIZKY; SAADAH SIREGAR; VISENSIUS KRISDIANILO; SITI KHADIJAH (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2024)
Soursop leaf (Annona muricata Linn) has flavonoid, alkaloid, and saponin compounds that can be used as antibacterial. Based on the compounds contained in soursop leaves can be used as a hand antiseptic. Based on this study, an antiseptic gel formulation of soursop leaf (Annona muricata Linn) as antibacterial against Staphylococcus epidermidis bacteria with a carbomer 940 base was made. Antiseptic gel of soursop leaf extract was formulated with unequal extract concentrations, namely in the 1 3% formulation, the 2.6 % formulation. , formulation 3 9%, and formulation 4 12%. The antibacterial test used was the well diffusion method. The antiseptic gel was tested for its physical properties, namely organoleptic test, homogeneity test, dispersion test, and pH test. Antiseptic gel preparations that have antibacterial activity against Staphylococcus epidermidis bacteria are formulations 3 and 4 9% and 12% extracts which have a picture zone of 5 and 7 mm while the positive control has an inhibition zone of 12 mm. The results of the tests carried out on organoleptic tests, dispersion tests, pH tests, homogeneity tests were in accordance with the parameters of the gel preparation. From this study, it showed the ability of soursop leaves to inhibit the growth of Staphylococcus epidermidis bacteria. Soursop (Annona muricata Linn) leaf extract. Has antibacterial activity against Staphyloccus epidermidis bacteria with a concentration of 3% formulation 1, formulation 6% concentration 2, formulation concentration 9%, formulation concentration 12% 4. At a concentration of 3%, 6% has inhibitory power with a diameter of 3mm, and a concentration of 9% had an inhibitory power with an inhibitory diameter of 5mm, while the concentration of 12% had an inhibitory power with an inhibitory diameter of 7mm against the bacterium Staphyloccus epidermidis.